PENGARUH KOMBINASI PENYUNTIKAN OVAPRIM DAN PROSTAGLANDIN F 2 α (PGF 2 α) TERHADAP VOLUME SEMEN DAN KUALITAS SPERMATOZOA IKAN MOTAN (Thynnicthys thynnoides Blkr) - Sukendi Sukendi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
The aim of this research was to identify the effect of the best ovaprim andprostaglandin F2 α injection combination toward semen volume and spermatozoaquality of fish motan (Thynnicthys thynnoides Blkr). The research yielddemonstrated that the best injection combination was 75 % ovaprim + 25 %PGF2 α (0,525 ml ovaprim + 750 μg PGF2 α / kg of body), with a semen volume1,20 ml, spermatozoa concentration 224.54x 10 9/ml, spermatozoa viability 88,98% and spermatozoa motility 80,56 %)